Gpad and Fuzzy Logic based Assistance System for Disabled People - Mumbaikar, Harshal; Priya, Guga (International Journal of Engineering and Technology, 2018)
This paper presents an assistance system for differentially abled people. It consists of Fuzzy logic control system and GpaD hand gesture technique to provide smooth and automatic control of the wheelchair in the presence of obstacles. The ultrasonic sensor is used for detecting obstacles. Actions in forward, reverse, right and left directions are taken care by GpaD which is based on IR sensor. Fuzzy logic controls the breaking power. The breaking power is based on the speed of the wheelchair and the distance between the wheelchair and an obstacle. The main purpose of this paper is to improve the safety of the differentially abled people and can be supervised from long distances without anybodyâ€™s help.Â